Obstetric Hemorrhage and Risk of Cardiovascular Disease After Three Decades: A Population-based Cohort Study. Issue 3 (25th September 2021) - Ukah, U.V.; Platt, R.W.; Potter, B.J.; Paradis, G.; Dayan, N.; He, S.; Augera, N.
Abstract : ( BJOG . 2020;127:1489–1497) The association between pregnancy complications and future risk of cardiovascular disease has been well studied. But most studies have focused on the hypertensive disorders of pregnancy and gestational diabetes. Less examined is the effect of other common disorders of pregnancy, such as obstetric hemorrhage, on the risk of cardiovascular disease later in life. The aim of this study was to examine whether there is an increased risk of cardiovascular disease up to 3 decades after pregnancy with obstetric hemorrhage.